GAMBARAN KONDISI LINGKUNGAN KAMAR HUNIAN DAN PERSONAL HYGIENE DI ASRAMA AKADEMI KEBIDANAN BARUNA HUSADA SIBUHUAN KECAMATAN LUBUK BARUMUN KABUPATEN PADANG LAWAS TAHUN 2013 - Lili Sarfiah Harahap; indra chahaya; wirsal hasan (Lingkungan dan Kesehatan Kerja, 2014)
The environment room condition or dormitory is the condition of base for a group, generally for student or collegents. This condition based on the healthy of room or dormitory and personal hygiene.This research is descriptive and use survey method. The population of this research are all students of midwifery Academy that consists of 58 persons and all of population as a sample.The purpose of this research is to know the description of condition  dormitory environment and personal hygiene in dormitory of midwifery Academy Baruna Husada Sibuhuan Tahun 2013.Research it is found the condition of dormitory that’s the ventilatoni,humidity, lighting, already qualified health according to Permenkes No.829/ Menkes/ SK/ 1999 occupant density while not yet eligible, skin cleanliness, fashion cleanliness, a towel clienliness whose bad category, while the hand and nail cleanlines and the bed and cover bed clienlines whose moderate category are.It is expected to the managers of the dormitory midwifery Academy to provide the facilities of dormitory that already meet health requirements and keep the facilities well. Moreover, the persons of dormitory midwifery Academy to keep the skin clienliness to avoid from skin disease.